An Overview: Nipah Virus Infection in Humans - Ashwini Jadhav; Shubham Choudhary; Aishwarya Mandhare; Sagar Adak; Sandip Kshirsagar (Journal of Global Pharma Technology, 2018)
Nipah viruses (NiV) are emerging zoonotic viruses that cause severe and often lethal respiratory illness and encephalitis in humans. Henipaviruses can infect a wide range of species and human-to-human transmission has been observed for NiV. Nipah virus is an emerging zoonosis with the potential to cause significant morbidity and mortality in humans and major economic and public health impacts. According to World Organization for Animal Health (Office International des Epizooties: OIE), Nipah virus is a notifiable disease of importance to international trade.Keywords: Nipah virus, respiratory tract, CNS.